2001
DOI: 10.1007/s11627-001-0129-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro rooting of almond (Prunus dulcis Mill.)

Abstract: Shoot cultures of the paper shell almond (Prunus dulcis Mill.) cultivars 'Ne Plus Ultra' and 'Nonpareil' were subcultured for 4 wk at 48C on growth regulator-free basal medium under low light conditions. Elongated shoots were excised and their response to a range of rooting treatments determined. Various concentrations of indole-3-butyric acid (IBA) and anaphthaleneacetic acid were compared over a range of incubation periods to determine the optimum auxin for root formation. In addition, the effect of shoot ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…Although successful tissue culture protocols have been reported for the juvenile explant of some almond cultivars (3,5,21,23,31), the published reports, especially for mature almond cultivars (1,3,7,23,33) still need to be improved due to the problems faced with in vitro rooting of micropropagated microshoots. Attempts to improve the in vitro rooting of "nonpareil" and "Ne Plus Ultra" cultivars by assessing the influences of several culture requirements was reported by Ainsley et al (2). Sixty percent rooting have been observed in both "nonpareil" and "ne Plus Ultra" cultivars using explants immersed for 12 h in water-agar 6 mg·l -1 with 1.0 mmol·l -1 indole-3-butyric acids (iBA) followed by incubation of microshoots in auxinfree basal media including 100.0 mol·l -1 pholoroglucinol (PG).…”
Section: Introductionmentioning
confidence: 99%
“…Although successful tissue culture protocols have been reported for the juvenile explant of some almond cultivars (3,5,21,23,31), the published reports, especially for mature almond cultivars (1,3,7,23,33) still need to be improved due to the problems faced with in vitro rooting of micropropagated microshoots. Attempts to improve the in vitro rooting of "nonpareil" and "Ne Plus Ultra" cultivars by assessing the influences of several culture requirements was reported by Ainsley et al (2). Sixty percent rooting have been observed in both "nonpareil" and "ne Plus Ultra" cultivars using explants immersed for 12 h in water-agar 6 mg·l -1 with 1.0 mmol·l -1 indole-3-butyric acids (iBA) followed by incubation of microshoots in auxinfree basal media including 100.0 mol·l -1 pholoroglucinol (PG).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of plant tissue to form adventitious roots depends on interaction of many exogenous and endogenous factors, including hormone. Most reports of adventitious root induction of woody species have involved treatments with exogenous auxins such as IBA, NAA or IAA (Ainsley et al, 2001). Exogenous auxins are only required at an early stage to stimulate emergence of new formed roots (Dobranszki and silva, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Channuntapipat et al (2003) showed that the maximum rooting of shoots for some almond hybrid rootstocks occurred on half strength MS medium with 2.4 mgL -1 IBA. Ainsley et al (2001) determined that IBA and NAA are the most suitable auxin for rooting seedlings of 'Nec plus ultra' and 'Nonpariel' almond cultivars, in vitro conditions.…”
Section: Hardening Offmentioning
confidence: 99%